Interest Changes and the Volatility of the UK Stock Market: Comparing Different Monetary Policy Regimes - James Malcolm, Green (2006)
This paper is an examination of the volatility of the UK Stock Market in the eras of differing monetary policy regimes in the UK since 1984. It contains a brief review of the literature on the underlying financial theory on the impact of monetary policy surprises, on expectations in financial markets and on appropriate econometric techniques. Hypotheses are formed that, in the regime of inflation targeting, volatility in the UK stock market caused by unexpected changes in interest rates has reduced. These are tested in regression equations. We find that there is evidence that the daily returns from the index are not related to unexpected interest rate changes since the Bank of England was granted independence in 1997. We also find in OLS regressions that the relationship between unexpected interest rate changes and volatility no longer exists since inflation targeting was introduced in 1992. However, if the autoregressive and heteroscedastic properties of financial returns time series are taken into consideration, we are only able to confirm the relationship between volatility and unexpected interest rate changes in the monetary policy regime of Monetary Aggregate Targeting, which ended in 1987.